Substrate-borne vibratory communication during courtship in Drosophila melanogaster. - Fabre, C; Hedwig, B; Conduit, G; Lawrence, P; Goodwin, S; Casal, J (2012)
Courtship in Drosophila melanogaster has become an iconic example of an innate and interactive series of behaviors. The female signals her acceptance of copulation by becoming immobile in response to a male's display of stereotyped actions. The male and female communicate via vision, air-borne sounds, and pheromones, but what triggers the female's immobility is undetermined. Here, we describe an overlooked and important component of Drosophila courtship. Video recordings and laser vibrometry show that the male abdomen shakes ("quivers"), generating substrate-borne vibrations at about six pulses per second. We present evidence that the female becomes receptive and stops walking because she senses these vibrations, rather than as a response to air-borne songs produced by the male fluttering the wings. We also present evidence that the neural circuits expressing the sex-determination genes fruitless and doublesex drive quivering behavior. These abdominal quivers and associated vibrations, as well as their effect on female receptivity, are conserved in other Drosophila species. Substrate-borne vibrations are an ancient form of communication that is widespread in animals. Our findings in Drosophila open a door to study the neuromuscular circuitry responsible for these signals and the sensory systems needed for their reception.